Increasing Student Learning Participation in Social Sciences Subjects through the RACVi (Reading, Analyze, Collecting Data, Virtualize) Model in SMPN 1 Garum - Inna Qurrota A'yun; Bayu Kurniawan; Jefferi Mohamed Lazim (UIN Fatmawati Sukarno Bengkulu, 2025)
The low learning participation of students at SMPN 1 Garum. Based on this problem, this research applies the RACVi learning model because the learning model is believed to be appropriate in optimizing the learning participation of class VIII students in social studies subjects. The purpose of this study is to optimize learning participation in social studies subjects of class VIII students at SMPN 1 Garum, Blitar Regency through the RACVi learning model. The research design used in this research is a spiral model classroom action research. The data collection techniques applied are observation and questionnaires. While the data analysis technique uses qualitative data analysis flowing models by Miles and Huberma, namely: data reduction, data presentation, and drawing conclusions. The results of this study indicate that classroom action research applied in two phases states that there is an increase in student learning participation through the application of the RACVI learning model. Based on observation data, the level of student participation for phase 1 was recorded at 72%. After improvements were made in cycle 2, the participation level increased to 81%. While the observation data from the questionnaire results also showed a trend of increasing student learning participation. In cycle 1, the level of student participation was recorded at 74%, and increased to 82% for phase 2. This data further strengthens the finding that the RACVI learning model is able to create a more interactive learning atmosphere. This proves that the implementation of this model can support a significant increase in student participation.